Prospective surveillance of neonatal meningitis. Issue 1 (July 1993) - Hristeva, L; Booy, R; Bowler, I; Wilkinson, A R
Abstract : Neonatal meningitis is a serious problem with a high mortality and frequent neurological sequelae. The incidence of neonatal meningitis was calculated and the aetiology, clinical and laboratory features, and the treatment of cases recorded prospectively over a 7 year 8 month period was documented. It was further investigated whether secondary meningitis had occurred after lumbar puncture. The estimated incidence of bacterial, viral, and fungal meningitis was 0.25, 0.11, and 0.02 per 1000 live births respectively. There were eight cases of early onset meningitis (seven definite, one probable) and group B streptococci accounted for six (75%) of these. Blood cultures were negative in only one of seven cases of definite early bacterial meningitis. Of the 15 late onset cases, Gram negative organisms accounted for six of the seven bacterial cases. The overall mortality was 26%. Of the 11 survivors of bacterial meningitis, three (27%) had significant neurological sequelae at follow up (between three months to three years later). As in the first 48 hours after birth an initial blood culture is unlikely to be negative if bacterial meningitis is present, lumbar puncture can be deferred if the procedure might exacerbate respiratory distress. Although approximately 1880 infants had a lumbar puncture during the review period, only one case of meningitis was found where it was possible that lumbar puncture in a bacteraemic infant may have caused meningeal infection. The incidence of this potential complication must therefore be low.